Miliary tuberculosis in a paediatric patient with psoriasis. Issue 3 (9th March 2021) - Kilgore, Jacob; Pelletier, Jonathon; Becken, Bradford; Kenny, Stephen; Das, Samrat; Parnell, Lisa
Abstract : We present a 16-year-old girl with a history of well-controlled psoriasis, on immunosuppression, who sought evaluation in the emergency department for 4 months of fever, cough and unintentional weight loss. The patient had seen multiple providers who had diagnosed her with community-acquired pneumonia, but she was unimproved after oral antibiotic therapy. On presentation, she was noted to be febrile, tachycardic and chronically ill-appearing. Her chest X-ray showed diffuse opacities and a right upper lobe cavitary lesion concerning for tuberculosis. A subsequent chest CT revealed miliary pulmonary nodules in addition to the cavitary lesion. The patient underwent subsequent brain MRI, which revealed multifocal ring-enhancing nodules consistent with parenchymal involvement. The patient was diagnosed with miliary tuberculosis and improved on quadruple therapy. Though rates of tuberculosis are increasing, rates remain low in children, though special consideration should be given to children who are immunosuppressed.